AI dalam Dunia Seni Digital: Kritik, Polemik, dan Aktivisme Media Sosial melalui Gerakan #TolakGambarAI - Rosyidah, Erna Dyah Luthfi (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2025)
Digital art is increasingly influenced by artificial intelligence (AI), presenting both creative opportunities and ethical polemics within the digital media ecosystem. This research aims to examine how AI influences the creative process of artists and how the #TolakGambarAI movement functions as a form of digital activism on social media. The method used is a systematic literature review of academic articles published between 2020 and 2024 from the Scopus and Google Scholar databases and then supplemented by public discourse on Twitter posts related to #TolakGambarAI to test the relevance of theoretical findings to digital communication practices. The results show that the debate surrounding AI-based art is divided into two main poles: AI is viewed as an instrument for the democratization of art that expands creative participation, and simultaneously as a threat that reduces originality and infringes on copyright. #TolakGambarAI movement demonstrates how artists use social media to build a discourse of resistance, mobilize support, and negotiate artistic identity amidst the tide of digitalization. This study confirms that resistance to AI is not related to the issue of art, but is also a practice of digital communication that reflects the dynamics of power, legitimacy, and media literacy in the online public sphere.